Accuracy of the DIAGNOcam and bitewing radiographs in the diagnosis of cavitated proximal carious lesions in primary molars - Alamoudi, N; Khan, J; El-Ashiry, E; Felemban, O; Bagher, S; Al-Tuwirqi, A (Nigerian journal of clinical practice, 2019)
Aims: To evaluate the diagnostic abilities of near-infrared light transillumination (using the DIAGNOcam) and bitewing radiographs in detecting cavitated proximal carious lesions in primary molars. Subjects and Methods: The study was a cross-sectional analytical, clinical study. The proximal surfaces of primary molars of healthy 5- to 8-year-old children were radiographically screened for the presence of carious lesions in the enamel or outer third of dentin (D1). Two trained and calibrated examiners evaluated the depth of caries in bitewing radiographs and DIAGNOcam images and then verified the presence of cavitation by direct visual examination using the "International Caries Detection and Assessment System" after temporary tooth separation. Results: A total of 236 proximal lesions were included in the study. Most of the clinically cavitated lesions (51.9%) were D1 radiographically and in outer dentin lesions (scores 3 and 4) by the DIAGNOcam (37% and 48.1%, respectively). Although DIAGNOcam showed higher sensitivity (0.852) compared to the radiographs (0.519), it showed slightly less specificity (0.569) compared to the radiographs (0.579). However, DIAGNOcam showed higher value of the area under the curve (AUC = 0.722; P < 0.001) compared to the radiographic method (AUC = 0.561; P = 0.308). Conclusions: The DIAGNOcam showed higher sensitivity and better accuracy than bitewing radiographs in diagnosing cavitated proximal lesions in primary molars and can be generally considered as an alternative to radiographs to detect cavitation without the hazards of ionizing radiation in children.